Geomorphological Study of the Karstic spring “Al Gamka” “North of Safita” (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research define and study geomorphological properties of the Karstic spring nameled “Al Gamka” , characterized one of seasonal springs that flux up as “fontain” .For this issue, we achieved a detailed geological and geomorphological Study in the region of spring, in addition to the field measures to draw and define the main karstic paths and its tributaries, which recharge this spring by groundwater coming from north-east side. To show the changes happened to the spring path, and to control water level variations inside this karstic paths and tributaries and the relation with groundwater influx periods through this “fountain”.This study showed reasons that led to groundwater influx through this spring with high discharge, and the relation between this spring discharge with the amount of precipitation on the recharge area. Finally, I presented detailed explanation about karstic extension, Which recharge this spring, in addition to the geomorphological development of the spring region through previous times.